THE FUNCTION OF DISCOURSE IN THE STRUCTURE OF A WORK OF ART: Yangi O'zbekiston taraqqiyotida tadqiqotlar o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Therefore, artistic discourse can be defined as the process of interaction between the text and the reader. An artistic text is one of the components of an act of artistic communication, representing a special artistic reality, which, combining with the discourses of the author and the reader, creates a new type of discourse - artistic. Yu. Lotman believed that the space of artistic discourse acts as a necessary intermediary between literature and language, between literature and external reality